Deployment of SLAM, navigation, and exploration onto a delivery robot - Ye, Jia Hui (Nanyang Technological University, 2023)
In this report, we present an integrated system for food delivery robotic research, focusing on mapping, localization, and navigation capabilities. The proposed system combines state-of-the-art techniques in SLAM, navigation, and exploration to develop an efficient and reliable solution for autonomous food delivery robots operating in urban environments. We leverage the LOAM algorithm for lidar-based SLAM, providing accurate and real-time mapping and localization. The CMU-navigation system is employed to handle autonomous navigation, with emphasis on local planning and terrain analysis for safe and efficient path following. The DSV planner, as part of the CMU-exploration system, is incorporated for exploration and relocation stages, allowing the robot to effectively navigate and adapt to dynamic environments. The report discusses the implementation, integration, and testing of the proposed system, both in simulation and real-world environments, demonstrating its potential for enhancing the capabilities of food delivery robots. The results highlight the system's robustness, accuracy, and adaptability, paving the way for further development and deployment in real-world applications.